Molecular indentification of Taenia asiatica - A new human Taeniid species for Vietnam - Hoa, Le Thanh; Nga, Nguyen Bich; De, Nguyen Van; Cong, Le Dinh; Doanh, Nguyen Quoc (Academia Journal of Biology, 2015)
Molecular indentification of Taenia asiatica - A new human Taeniid species for Vietnam